A Critical Review on the Book The Structure of Scientific Revolutions - Farhang Ershad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The aim of Thomas Kuhn in writing The Structure of Scientific Revolutions was to prepare an analysis in the field of the philosophical history of science and to explain the changes and continuity of scientific institutions. He studied physics at Harvard University but he was more interested in philosophy of science history. Kuhn’s mind was deeply impressed by Alexandre Koyre´, Max Planck, and James Conant, also his interest in hermeneutics was motivated by Ludwig Wittgenstein and Stanley Cavell. This book which was really innovative in its own time (1969s) brought about some important concepts that most frequented ones would be “paradigm” and “scientific community”. For Kuhn, the relations between these two concepts had an important role in the development of the sociology of science. Perhaps it could be said that the same as Kuhn was influenced by his predecessors, his posterities were impressed by Kuhn in their views in the field of sociology of science.